Does transformational leadership encourage organizational commitment? - Roby Sambung; Ricky Kristiawan; Olivia Winda Ony Panjaitan (Jurnal Inovasi Ekonomi, 2021)
This study aims to determine whether job satisfaction mediates the relationship between transformational leadership and the organizational commitment of civil servants. A structural equation modelling approach was used to test the collected data with a sample of 51 respondents. The results show that job satisfaction can mediate the relationship between transformational leadership and organizational commitment.